The Relationship between Customer Satisfaction and Loyalty: A Systematic Literature Review - Budi Utami; M. Syamsul Hidayat; Eny Setyariningsih (International Journal of Social Service and Research (IJSSR), 2023)
Customer behavior in making decisions to purchase goods or services is always dynamic. The satisfaction obtained by customers ultimately leads to loyalty to the product or service. There are several studies and discussions that still have different results regarding the relationship between customer satisfaction and customer loyalty. Therefore, the goal This article aims to provide a clearer understanding of the relationship between satisfaction and customer loyalty by conducting a systematic literature review of 200 Scopus indexed publications. From these 200 articles, we selected a minimum of 95 citations. Then we further selected 23 relevant publication articles. from 2011 to 2022.The results of the analysis identify in general that customer satisfaction has a relationship and influence on customer loyalty.